(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This qualitative study explores the perceptions and experiences of Saudi educators regarding the integration of Artificial Intelligence (AI) in classroom teaching. Through semi-structured interviews with a purposively sampled group of teachers, the research investigates initial experiences with AI, anticipated changes in teaching roles, support and training needs, student reactions, and concerns about long-term AI integration. Employing a constructivist grounded theory approach, the study reveals a nuanced understanding of the opportunities and challenges presented by AI in education. Findings indicate a spectrum of initial responses to AI integration, ranging from enthusiasm to apprehension, emphasizing the need for comprehensive professional development and robust support systems. Educators anticipate significant shifts in their pedagogical roles, foreseeing AI as a facilitator of personalized learning but also expressing concerns about its potential to marginalize traditional teaching practices. Student reactions were generally positive, though mixed, highlighting the need for adaptive AI implementation strategies. Concerns about ethical implications and educational equity were prominent, underscoring the necessity of a balanced, ethical approach to AI deployment. The study contributes to the emerging body of literature on AI in education and offers insights for policymakers, curriculum developers, and educational technologists on effectively harnessing AI’s potential while addressing its challenges. It calls for ongoing dialogue, professional development, and ethical considerations as AI becomes more integrated into educational systems, ensuring it serves as a supportive component within the pedagogical framework.